2021
DOI: 10.1089/dna.2020.6271
|View full text |Cite
|
Sign up to set email alerts
|

Trophectoderm Mitochondrial DNA Content Associated with Embryo Quality and Day-5 Euploid Blastocyst Transfer Outcomes

Abstract: Mitochondria play a critical role in cell function and embryo development. Recently, increasing studies have investigated whether mitochondrial DNA (mtDNA) can be used as a predictive biomarker of embryo implantation. However, the results of its effect on implantation are still controversial. To further understand the clinical application value of mtDNA content for reproductive potential, we analyzed the influence of relative mtDNA quantity on embryo quality and transfer outcomes based on the results of second… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(28 citation statements)
references
References 29 publications
7
21
0
Order By: Relevance
“…obtained the opposite results that mtDNA content decreased with advancing age ( 31 ). Other studies found no relation with maternal age ( 28 , 34 , 57 ), which is consistent with our finding. Although the hypothesis that reproductive ageing in older women is associated with the content of mtDNA in blastocyst-stage embryos is attractive ( 27 ), our results do not support this argument.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…obtained the opposite results that mtDNA content decreased with advancing age ( 31 ). Other studies found no relation with maternal age ( 28 , 34 , 57 ), which is consistent with our finding. Although the hypothesis that reproductive ageing in older women is associated with the content of mtDNA in blastocyst-stage embryos is attractive ( 27 ), our results do not support this argument.…”
Section: Discussionsupporting
confidence: 93%
“…Although the hypothesis that reproductive ageing in older women is associated with the content of mtDNA in blastocyst-stage embryos is attractive ( 27 ), our results do not support this argument. We also found that blastocysts biopsied on Day 5 showed higher levels of mtDNA content compared with those biopsied on Day 6, which was consistent with previous studies ( 33 , 55 , 57 , 66 ). The replication of mtDNA will not be reactivated in the embryo until the blastocyst stage ( 67 ), blastocysts biopsied on Day 6 may undergo more cell divisions compared with blastocysts biopsied on Day 5, which may result in a reduction of mtDNA content in Day 6 blastocysts.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…As most of published studies concerning mtDNA copy number in human embryos were conducted using blastocysts from frozen IVF cycles [7][8][9][10][11][12][13]36], we decided to evaluate the end point parameters by assessing blastomeres biopsied at the cleavage stage that were transferred on day 5 of the same cycle. We aimed to evaluate the significance of the energy production process at such an early stage of embryo development.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years, several studies have been performed to evaluate mtDNA as a potential biomarker of embryo vitality. However, there is a lot of controversy as studies performed have reached contradicting conclusions [4,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%